Post-Divorce Determination Of Marriage Dispensation: Penetapan Dispensasi Perkawinan Pasca Perceraian - Inayatul Anisah; Ana Laela Fatikhatul Choiriyah; Achmad Walif Rizqy; Nur Fitriah (Indonesian Journal of Law and Islamic Law (IJLIL), 2023)
The marriage law in force in Indonesia shows the parameters of maturity when a person is deemed capable of getting married, since the enactment of Law Number 16 of 2019 amendments to Law Number 01 of 1974 concerning registration, applications for dispensation for marriage in religious courts are increasing every year . Likewise in the Bondowoso Religious Court, along with the increase in requests for marital dispensation also accompanied by children who have applied for marital dispensation after some time later filing for divorce, so that in this case the divorce claims experienced a significant increase after the revocation of the marital dispensation was enacted. There are things that the government needs to do in responding to these conditions, namely: massive legal dissemination regarding the impact of early marriage and protection for women after divorce. It is on this basis that the author wishes to review divorce after the determination of marital dispensation using an empirical juridical research methodology.